Media discourse : representation and interaction - Talbot, Mary (Media topics., 2007)
This lively and accessible study of media and discourse combines theoretical reflection with empirical engagement, and brings together insights from a range of disciplines. Within media and cultural studies, the study of media texts is dominated by an exclusive focus on representation. This book adds long overdue attention to social interaction. The book is divided into two sections. The first outlines key theoretical issues and concepts, including informalisation, genre hybridisation, positioning, dialogism and discourse. The second is a sustained interrogation of social interaction in and around media. Re-examining issues of representation and interaction, it critically assesses work on the para-social and broadcast sociability, then explores distinct sites of interaction: production communities, audience communities and 'interactivity' with audiences. Key Features The book is rich with fascinating examples involving British and US media, including radio, television, magazines and newspapers and their Internet spin-offs. It brings together insights from conversation analysis, critical discourse analysis, cultural studies and media anthropology. It is key reading for advanced undergraduates and postgraduates doing media studies, communication and cultural studies and journalism studies.